2009
DOI: 10.1504/ijpd.2009.023323
|View full text |Cite
|
Sign up to set email alerts
|

Applications of converged networks in construction

Abstract: Abstract:Converged networks which carry voice, video and data have promised cost savings for its users. Much of the construction industry spends over £1 million on communication, mainly from the construction sites to headquarters. With the use of IP telephony and converged networks, the cost can be reduced significantly. Using existing 802.11b/g wireless networks, access to the voice network can be delivered on a construction site allowing mobile users access to personnel as well as data instantly.Voice over I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Ahsan et al [30] studied the storage of communications produced during a project life and concluded that the importance of email usage increased in communicating and storing major information. Another study by Elamin et al [31] used different criteria in evaluating project communication tools and categorized email as an effective technique to track, store, and extract progress data.…”
Section: Email-servicesmentioning
confidence: 99%
“…Ahsan et al [30] studied the storage of communications produced during a project life and concluded that the importance of email usage increased in communicating and storing major information. Another study by Elamin et al [31] used different criteria in evaluating project communication tools and categorized email as an effective technique to track, store, and extract progress data.…”
Section: Email-servicesmentioning
confidence: 99%